SIMS U–Pb study of zircon from Apollo 14 and 17 breccias: Implications for the evolution of lunar KREEP - Nemchin, Alexander; Pidgeon, Robert; Whitehouse, M.; Vaughan, Jeffrey Patrick; Meyer, C. (Pergamon-Elsevier Science Ltd, 2008)
We report the results of a SIMS U–Pb study of 112 zircons from breccia samples from the Apollo 14 and 17 landing sites. Zircon occurs in the breccia matrices as rounded, irregular shaped, broken and rarely euhedral grains and as constituent minerals in a variety of lithic clasts ranging in composition from ultra-mafic and mafic rocks to highly evolved granophyres. Crystallisation of zircon in magmatic rocks is governed by the zirconium saturation in the melt. As a consequence, the presence of zircon in mafic rocks on the Moon implies enrichment of their parent melts in the KREEP component. Our SIMS results show that the ages of zircons from mafic to ultramafic clasts range from ca. 4.35 Ga to ca. 4.00 Ga demonstrating multiple generations of KREEPy mafic and ultramafic magmas over this time period. Individual zircon clasts in breccia matrices have a similar age range to zircons in igneous clasts and all represent zircons that have been incorporated into the breccia from older parents. The age distributions of zircons from breccias from both the Apollo 14 and Apollo 17 landing sites are essentially identical in the range 4.35–4.20 Ga. However, whereas Apollo 14 zircons additionally show ages from 4.20 to 3.90 Ga, no zircons from Apollo 17 samples have primary ages less than ca. 4.20 Ga.Also, in contrast to previous suggestions that the magmatism in the lunar crust is continuous our results show that the zircon age distribution is uneven, with distinct peaks of magmatic activity at ca. 4.35 Ga, ca. 4.20 Ga in Apollo 14 and 17 and a possible third peak in zircons from Apollo 14 at ca. 4.00 Ga. To explain the differences in the zircon age distributions between the Apollo 14 and 17 landing sites we propose that episodes of KREEP magmatism were generated from a primary reservoir, and that this reservoir contracted over time towards the centre of Procellarum KREEP terrane. We attribute the peaks in KREEP magmatism to impact induced emplacement of KREEP magma from a primary mantle source or to a progressive thermal build-up in the mantle source until the temperature exceeds the threshold for generation of KREEP magma, which is transported into the crust by an unspecified possibly plume-like process.